Numerical Simulation of Fractional Control System Using Chebyshev Polynomials. (13th December 2018) - Zhang, Jun; Li, Yugui; Xie, Jiaquan
Abstract : In the current study, a numerical scheme based on Chebyshev polynomials is proposed to solve the problem of fractional control system. The operational matrix of fractional derivative is derived and that is used to transform the original problem into a system of linear equations. Lastly, several numerical examples are presented to verify the effectiveness and feasibility of the given method.